The effect of creative problem solving with the intervention social skills on the performance of creative tasks - Suryanto, Hadi; Degeng, I Nyoman Sudana; Djatmika, Ery Tri; Kuswandi, Dedi (Creativity Studies, 2021)
This research aims to determine the social skills intervention with the student’s ability to solve problems creatively towards understanding the concepts and procedures: the objectives of learning. A quasi-experimental research design was used to see the interaction between attitudes and treatments. The research sample was students who took computer courses in reality-based laboratories in vocational schools. Data analysis was performed using descriptive analysis techniques and inferential statistical multivariate analysis of variance two paths. Creative problem solving is intervened by a background in social skills to understand concepts and procedures. Social skills have a greater influence on the creative process. This can be seen when giving creative problem-solving tasks. The abilities they have, about; readiness to learn, the ability to understand one’s own needs, and the ability to understand one’s own learning style, greatly support the performance of their creative assignments. At the same time, external factors have less influence on the performance of creative tasks. These external factors are influenced by the class social environment, group formation, and class management. Students who have high social skills find it easier to complete creative tasks, and students who have low social skills have problems adapting and adjusting to the learning process.